2019
DOI: 10.1016/j.heliyon.2019.e02984
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic and distributional impacts of exchange rate devaluation in Ethiopia: A computable general equilibrium approach

Abstract: In this paper, we simulate the macroeconomic and distributional impacts of exchange rate devaluation in Ethiopia using a dynamic single country Computable General Equilibrium model. We find that although devaluation helps exports to be more competitive in the short term, thereby increasing export earnings, over the long term the policy is found to have a contractionary and inflationary impact in a developing country like Ethiopia. It also comes at the cost of a reduction in household welfare and investment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
2
17
1
Order By: Relevance
“…The same results found by (Laryea & Sumaila, 2001;Loening et al, 2009) indicated that the exchange rate has a positive impact on inflation. Another study by Woldie and Siddig (2019) showed that in the long-run devaluation of the exchange rate has an inflationary impact and contrary, Ambachew et al (2012) indicated that the depreciation of exchange rate decreases inflation. Similarly, Nigusse et al (2019) in their study proved devaluation reduces inflation while appreciation of real effective exchange rate triggers inflation in in Ethiopia.…”
Section: Maximum Lag Selectionmentioning
confidence: 97%
See 1 more Smart Citation
“…The same results found by (Laryea & Sumaila, 2001;Loening et al, 2009) indicated that the exchange rate has a positive impact on inflation. Another study by Woldie and Siddig (2019) showed that in the long-run devaluation of the exchange rate has an inflationary impact and contrary, Ambachew et al (2012) indicated that the depreciation of exchange rate decreases inflation. Similarly, Nigusse et al (2019) in their study proved devaluation reduces inflation while appreciation of real effective exchange rate triggers inflation in in Ethiopia.…”
Section: Maximum Lag Selectionmentioning
confidence: 97%
“…Another study by Rashid (2010) linked the sharp rise in domestic inflation to general demand, apart from a few exceptional cases between 2007-08, when cereal production was much lower than official agricultural statistics. Besides the supply and demand factors, other factors such as money supply, high government spending, real interest and shocks in key economic sectors such as agriculture (Bane, 2018), devaluation of Ethiopia's birr (Woldie & Siddig, 2019) were identified as the sources of inflation in Ethiopia. Most importantly, Durevall et al (2013), concluded that inflation in Ethiopia is strongly related to food inflation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…3 Cited in Agénor and Montiel (2015, p. 111), which provides an elaborate discussion on the topic. 4 See, among others, Woldie and Siddig (2019) for evidence on the negative (contractionary and inflationary) effects of exchange rate devaluation in Ethiopia. 5 The generation of structuralist models of inflation of the 1980 s considers inflation as the outcome of conflict (or bargaining) between workers and capitalists over the distribution of income between wages and profits (Cardoso, 1981;Taylor, 1983;Taylor, 1991).…”
Section: Data Availability Statementmentioning
confidence: 99%
“… See, among others, Woldie and Siddig (2019) for evidence on the negative (contractionary and inflationary) effects of exchange rate devaluation in Ethiopia. …”
mentioning
confidence: 99%
“…Therefore, the Central Bank in developing countries actively uses monetary policy to stabilise the exchange rate and avoid high volatility [10]. Exchange rate volatility is defined as large fluctuations around the balance value or short-term fluctuations around the exchange rate's long-term trends [11][12][13]. Also, exchange rate volatility is associated with unpredictability in the economy's relative prices.…”
Section: Introductionmentioning
confidence: 99%